PENGARUH MODEL PEMBELAJARAN REINFORCEMENT UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA SMPN 1 BONGGAKARADENG TANA TORAJA PADA MATERI BERBAGAI SISTEM DALAM KEHIDUPAN MANUSIA - Isnada, Isnada (Jurnal Biotek, 2015)
This study aimed to determine students learning outcome biology using model Reinforcement. This study is classified as a type of quasi-experimental study aimed to look at the effect of reinforcement in improving student learning outcomes in the subject of Biology subjects understand the different systems in the human life. Quasi-experimental research methods using models contol nonequivalent group design. Based on the results of research in the field, shows that the administration of reinforcement (reinforcement) can significantly improve student learning outcomes of the acquisition value of the average (mean) of 47.17 pretest and post-test gain of 86.33.